The influence of the diacetylenic group on the properties of three-dimensional polymers - Yu. M. Sivergin; S. M. Kireeva (Тонкие химические технологии, 2014)
This paper describes the synthesis and the study of oligomers of bis(methacryloyl-oxy-1-hexamethylene-6-oxy)- ortho-phthaloyl (MHM-o-Ph) and its analog bis(methacryloyl-oxy-1-hexa-2,4-diyn-6-oxy)-ortho-phthaloyl (MHD-oPh) containing conjugated triple bonds in the oligomeric block. Besides the properties of polymers based on these oligomers were investigated. The polymerization of MHD-o-Ph conditions the formation of a bi-three-dimensional polymer, the skeleton of which contains a three-dimensional network of polymethacrylate macrochains and a network with a system of conjugated bonds. This system significantly affects the complex of the polymeric properties.